Mapping Digital Citizenship among Resettled Refugees’ Social Media Use in New Zealand - Marlowe, Jay; Malihi, Arezoo; Cabalquinto, Earvin; Mei, Bing; Nasier, Bilal; Rai, Parbati; Maang, Dennis; Mazraeh, Yousef; Mattar, Mohammad; Marcela Agudelo Cardona , Sandra; NurMuhammad , Rizwangul; Sheika, Yahya; et al. (New Zealand Sociology, 2024)
In an increasingly digital world, refugees heavily rely on modern communication technologies to navigate many aspects of their lives. In this paper, we specifically explore how resettled refugees in New Zealand use social media in their everyday lives. We present the findings drawn from a national survey (N=592) in six languages, exposing the benefits and limits of social media use among this cohort of people. Using a multivariate model, we show how refugees’ social and political activities enable civic participation and a sense of belonging. Our study also charts the barriers constraining their everyday social media use, including financial cost, security concerns, and low levels of technical and digital literacy. By centring the impacts of socio-demographics and socio-technological factors, we interrogate the meanings and outcomes of digital exclusion, which is crucial for informing digital citizenship and settlement policy among resettled refugees.